Proximate composition and microbial quality of three imported aquarium fish feeds in Bangladesh (Bangladesh Journal of Zoology, 2015)
Proximate composition and microbial quality of three aquarium fish feeds commonly found in Bangladesh were collected from fish feed market of Dhaka city. Significantly higher moisture content (2.12 ± 0.06%) was found in Super NovaTM fish feed while similar moisture content was detected in other two feeds (p